Interpreting and translating Shakespeare's heraldic terminology: 1 Henry IV and 2 Henry VI in Slovene - Gadpaille, Michelle (Annales. Series historia et sociologia, 2020)
William Shakespeare reflected the Elizabethan fascination with the intricate symbolism of heraldry in his poetry and drama. This paper examines Slovene translations of selected passages from 1 Henry IV and 2 Henry VI that involve heraldic language and pose conundrums even in the original. Because of a scarcity of available vocabulary in the target language, translator Matej Bor struggled to replicate heraldic allusions and puns; nevertheless, he successfully compensated for the lexical gap with other structures. The paper also proposes a new reading of a crucial heraldic allusion from 2 Henry VI.
Keywords: angleška književnost; drama; dramatika; English literature; heraldic symbolism; heraldična simbolika; poetry; poezija; prevodi; Shakespeare, William; translation